LncRNA‐mediated posttranslational modifications and reprogramming of energy metabolism in cancer - Tan, Yue‐Tao; Lin, Jin‐Fei; Li, Ting; Li, Jia‐Jun; Xu, Rui‐Hua; Ju, Huai‐Qiang (Cancer communications (London, England), 2021)
Altered metabolism is a hallmark of cancer, and the reprogramming of energy metabolism has historically been considered a general phenomenon of tumors. It is well recognized that long noncoding RNAs (lncRNAs) regulate energy metabolism in cancer. However, lncRNA‐mediated posttranslational modifications and metabolic reprogramming are unclear at present. In this review, we summarized the current understanding of the interactions between the alterations in cancer‐associated energy metabolism and the lncRNA‐mediated posttranslational modifications of metabolic enzymes, transcription factors, and other proteins involved in metabolic pathways. In addition, we discuss the mechanisms through which these interactions contribute to tumor initiation and progression, and the key roles and clinical significance of functional lncRNAs. We believe that an in‐depth understanding of lncRNA‐mediated cancer metabolic reprogramming can help to identify cellular vulnerabilities that can be exploited for cancer diagnosis and therapy.